2008
DOI: 10.1002/tox.20454
|View full text |Cite
|
Sign up to set email alerts
|

Malathion‐induced alteration of the antioxidant defence system in kidney, gill, and intestine of Carassius auratus gibelio

Abstract: Pesticides such as malathion, commonly used in agriculture and households, are toxic substances that lead to reactive oxygen species generation, which harms organisms. Ecotoxicological consequences of malathion, particularly its effects on antioxidants in fish, are not well understood. Thus, we investigated the effects of malathion (0.05 mg/L) on lipid peroxidation and antioxidant systems in Carassius auratus gibelio kidney, intestine, and gills following exposure times of 1, 2, 3, and 6 days. The lipid peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 40 publications
(31 reference statements)
0
23
0
1
Order By: Relevance
“…Hai et al (1997) showed that GSH-Px activation is enhanced (approximately 200%) in brain of Cyprinus carpio exposed to dichlorvos. Likewise, GSH-Px activities were elevated (57%) in the livers of C. auratus exposed to 2,4-dichlorophenol (Zhang et al 2004) and to malathion (Huculeci et al 2008). The biological function of GSH-Px is to reduce H 2 O 2 and lipid hydroperoxides (Verma et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Hai et al (1997) showed that GSH-Px activation is enhanced (approximately 200%) in brain of Cyprinus carpio exposed to dichlorvos. Likewise, GSH-Px activities were elevated (57%) in the livers of C. auratus exposed to 2,4-dichlorophenol (Zhang et al 2004) and to malathion (Huculeci et al 2008). The biological function of GSH-Px is to reduce H 2 O 2 and lipid hydroperoxides (Verma et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Malathion has been shown to produce oxidative stress in somatic cells in fish, humans fetuses, and rats, altering the antioxidant defense system in erythrocytes, plasma, liver, pancreas, muscle, and brain …”
Section: Introductionmentioning
confidence: 99%
“…10 In previous studies, it was shown that malathion impairs oogenesis in mouse 8 and porcine oocytes by affecting viability and in vitro maturation (IVM), 11 in vitro fertilization and embryo development. 12 Malathion has been shown to produce oxidative stress in somatic cells in fish, humans fetuses, and rats, [13][14][15][16] altering the antioxidant defense system in erythrocytes, 17 plasma, 13 liver, 18 pancreas, muscle, and brain. 6,19 The mitochondria are the major target cell organelle of OPs as malathion.…”
mentioning
confidence: 99%
“…Therefore, evaluation of antioxidant enzymes activities and markers of free radical damage in the heart, liver, and kidney tissue are important for assessing F toxicity. Melatonin is known to have the ability to protect cells from free radical damage [1214]. Previous studies have shown that melatonin [12, 15] and buffalo epiphyseal proteins (BEP) have various physiological functions that might protect against fluoride and as-induced oxidative stress [1621].…”
Section: Introductionmentioning
confidence: 99%